Cerebral haemodynamics during arrhythmia in health, ischaemic heart disease and heart failure with reduced ejection fraction, and in a preclinical swine model. (4th May 2022) - Marshall, Rory A.; Luchkanych, Adam M. S.; Morton, Jude S.; Boyes, Natasha G.; Zhai, Alexander; Marciniuk, Darcy D.; Mei, Yixue; Allison, Elric Y.; Shoemaker, J. Kevin; Al‐Khazraji, Baraa K.; Allen, Matti D.; Tomczak, Corey R.; et al.
Abstract : Abstract: Ventricular arrhythmias are associated with neurological impairment and could represent a source of cerebral hypoperfusion. In the present study, data from healthy individuals ( n  = 11), patients with ischaemic heart disease (IHD; ejection fraction >40%; n  = 9) and patients with heart failure with reduced ejection fraction (HFrEF; EF = 31 (5)%, n  = 11), as well as data from swine surgeries, where spontaneous ventricular arrhythmias were observed during cerebrovascular examination (transcranial Doppler ultrasound in humans and laser Doppler in swine) were analysed retrospectively to investigate the effect of arrhythmia on cerebral microvascular haemodynamics. A subset of participants also completed the Montreal Cognitive Assessment (MoCA). Middle cerebral artery mean blood velocity (MCAVmean ) decreased during premature ventricular contraction (PVC) in all groups, and data from swine indicate PVCs reduced cerebral microvascular perfusion. Overall MCAVmean was decreased in the HFrEF vs . control group. Further, %∆MCAVmean /%∆mean arterial pressure during the PVC was greater in the HFrEF vs . control group and was correlated with decreased MoCA scores. Subanalysis of HFrEF data revealed that during bigeminy MCAVmean decreased owing to reductions during irregular beats only. During non‐sustained ventricular tachycardia, MCAVmean decreased but recovered above baseline upon return to sinus rhythm. Also, haemodynamic perturbations during and following the PVC were greater in the brachial artery vs . the MCA. Therefore, ventricular arrhythmias decreased indices of cerebral perfusion irrespective of IHD or HFrEF. The relative magnitude of arrhythmia‐induced haemodynamic perturbations appears to be population specific and arrhythmia type and organ dependent. The cumulative burden of arrhythmia‐induced deficits may exacerbate existing cerebral hypoperfusion in HFrEF and contribute to neurological abnormalities in this population. Key points: Irregular heartbeats are often considered benign in isolation, but individuals who experience them frequently have a higher prevalence of cerebrovascular and/or cognitive associated disorders. How irregular heartbeats affect blood pressure and cerebral haemodynamics in healthy and cardiovascular disease patients, those with and without reduced ejection fraction, remains unknown. Here it was found that in the absence of symptoms associated with irregular heartbeats, such as dizziness or hypotension, single, multiple non‐sustained and sustained irregular heartbeats influence cerebral haemodynamics in a population‐specific, arrhythmia‐type and organ‐dependent manner. Relative deficits in the index of cerebral blood flow normalized to relative deficits in blood pressure were greatest in patients with heart failure with reduced ejection and inversely related with cognitive performance. Chronic arrhythmias may exacerbate existing cerebral hypoperfusion in heart failure with reduced ejection fraction, thereby providing a mechanistic link between otherwise benign irregular heartbeats and cognitive dysfunction, independent of embolism. Abstract : Abstract figure legend In the present study, middle cerebral artery mean blood velocity (MCAVmean ; a surrogate for cerebral blood flow) was measured with transcranial Doppler ultrasound during normal sinus rhythm and ventricular arrhythmia in patients with ischaemic heart disease (IHD; with ejection fraction ≥40%), heart failure with reduced ejection fraction (HFrEF) and healthy age‐matched controls. The major findings reveal that whereas normal sinus rhythm is associated with stable MCAVmean, during bigeminy, premature ventricular contractions (PVC) and non‐sustained ventricular tachycardia MCAVmean decreased by 6–62%. Of note, deficits in %∆MCAVmean /%∆mean arterial pressure (MAP) during PVC were greater and cognitive performance was lower in HFrEF and increased %∆MCAVmean /%∆MAP was associated with poorer cognitive performance across the entire sample. A portion of this figure was created with biorender.com.